ENVIRONMENTAL EXPENDITURES OF IRON-PROCESSING ENTERPRISES OF KRYVYI RIH - Kosharna, S. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The development of industry and the consequences of the development have a negative effect on the environment, so legislative authorities are enforced to move from discussion of environmental problems to their actual solving. Accordingly, it is required to render more attention to, and provide monitoring of, industrial enterprises (specifically metallurgical ones, which are the largest environmental contaminants in Ukraine). Part of the financial resources of these enterprises must be allotted not only to meet the requirements presented in Section 3 of the Tax Code of Ukraine, which regulates taxes for environmental protection, but also to pay other reasonable environment-oriented expenditures. The subjects of the study are the data on the theoretical basis and study methods concerning environment-oriented expenditures, economic and organizational decisions chosen as the study objective one of the above-mentioned enterprises – ArcelorMittal Kryvyi Rih, and the geochemical characteristics of the environment in the areas near the enterprises. The offer of the new scheme of classification of environment-oriented expenditures on the base of existent classifications proposed by Savchenko O.F., Saienko K.S., and Tuiakova Z.S., and an offer of increasing of investments in the environmental education of the Kryvyi Rih region population in order to raise the level of environmental responsibility are presented in the paper. This paper contains the results of the comparative analysis of amounts and patterns of environment-oriented expenditures of the largest ore mining and metallurgical enterprises in the areas of their activities.